Ucronía y Utopía. Proyecto utópico de Pedro Henríquez Ureña - Durán, Diony (2010)
No Ateneu da juventude do México (1909) os escritores buscavam o estudo da cultura grega, o debate filosófico e especulavam sobre o futuro da Hispano-américa, sobretudo sobre o México. O Ateneu, o México, a cultura e revolução mexicana foram centros de aprendizagem e lançamento para jovens escritores, arquitectos, pintores; especialmente para o dominicano Pedro Henriquez Ureña (1884-1946). At the mexican youth Athenaeum (1909), writters developed the study of greek culture, the filosophical debate and speculated about the Hispanic-American future and above all Mexican one. The Athenaeum, Mexic, the culture and Mexican revolution were a learning and launching center for young writers, arquitects, painters; especially to the Dominican Pedro Henriquez Ureña (1884-1946).